The Effectiveness of Internet Cognitive Behavioural Therapy (iCBT) for Depression in Primary Care: A Quality Assurance Study - Williams, Alishia D (Public Library of Science, 2013)
BACKGROUND: Depression is a common, recurrent, and debilitating problem and Internet delivered cognitive behaviour therapy (iCBT) could offer one solution. There are at least 25 controlled trials that demonstrate the efficacy of iCBT. The aim of the current paper was to evaluate the effectiveness of an iCBT Program in primary care that had been demonstrated to be efficacious in two randomized controlled trials (RCTs). METHOD: Quality assurance data from 359 patients prescribed the Sadness Program in Australia from October 2010 to November 2011 were included. RESULTS: Intent-to-treat marginal model analyses demonstrated significant reductions in depressive symptoms (PHQ9), distress (K10), and impairment (WHODAS-II) with medium-large effect sizes (Cohen's d = .51–1.13.), even in severe and/or suicidal patients (Cohen's d = .50–1.49.) Secondary analyses on patients who completed all 6 lessons showed levels of clinically significant change as indexed by established criteria for remission, recovery, and reliable change. CONCLUSIONS: The Sadness Program is effective when prescribed by primary care practitioners and is consistent with a cost-effective stepped-care framework.